2018
DOI: 10.12968/bjon.2018.27.19.1121
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and clinical outcomes in cancer survivorship

Abstract: Increasing evidence points to the role of vitamin D (VD) supplementation in cancer management. A comprehensive search of online databases was undertaken for all research studies relating to VD supplementation in cancer survivorship published up to November 2017. Eighteen studies meeting the inclusion criteria were selected for this review, the majority of which involved supplementation in breast cancer. This review concludes that VD supplementation plays an important role in disease free survival (DFS) in a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
9
0
2
Order By: Relevance
“…Radiotherapy is one of the most effective and frequently used tumor treatments, however, both the radioresistance of tumors and the damage caused to healthy tissues nearby tumors under high-dose ionizing radiation, limit the use of radiotherapy. Natural and synthetic vitamin D compounds have been proven as anticancer agents ( Larriba and Munoz, 2005 ; Pervin et al., 2013 ; Feldman et al., 2014 ; Griffin and Dowling, 2018 ) . It has been reported that vitamin D and vitamin D analogs radiosensitized breast cancer and lung cancer cells through altering the nature of the autophagy, converting it from a protective form to a cytotoxic form in vitro ( Sundaram and Gewirtz, 1999 ; Demasters et al., 2006 ; Bristol et al., 2012 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy is one of the most effective and frequently used tumor treatments, however, both the radioresistance of tumors and the damage caused to healthy tissues nearby tumors under high-dose ionizing radiation, limit the use of radiotherapy. Natural and synthetic vitamin D compounds have been proven as anticancer agents ( Larriba and Munoz, 2005 ; Pervin et al., 2013 ; Feldman et al., 2014 ; Griffin and Dowling, 2018 ) . It has been reported that vitamin D and vitamin D analogs radiosensitized breast cancer and lung cancer cells through altering the nature of the autophagy, converting it from a protective form to a cytotoxic form in vitro ( Sundaram and Gewirtz, 1999 ; Demasters et al., 2006 ; Bristol et al., 2012 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies and experimental studies support that 1α dihydroxyvitamin D [1α,25(OH) 2 D 3 ] possesses anti-tumor actions in various cancers, such as breast-, colon-, and ovarian cancer ( Larriba and Munoz, 2005 ; Pervin et al., 2013 ; Feldman et al., 2014 ; Griffin and Dowling, 2018 ). Additionally, low 25(OH)D serum was associated with higher ovarian cancer susceptibility and a poor prognosis for patients with lung cancer ( Ong et al., 2016 ; Akiba et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also still a lack of evidence for public health recommendation for using vitamin D for patients with breast cancer, and vitamin D status is recognized as an important parameter when antiestrogen treatment causes joint pain and AI-associated arthralgia or aggravates osteoporosis [15]. Many clinical studies investigating the role of vitamin D intake during breast cancer treatment are inconclusive and have often ignored the fact that other vitamin D metabolites, in addition to the most frequently analysed, i.e., 25(OH)D 3 or 1,25(OH) 2 D 3 , arise in the body after vitamin D supplementation and some of these metabolites are active [13,[49][50][51][52][53]. As shown by A. Verma et al, together with vitamin D metabolites such as (24R)-24,25(OH) 2 D 3 , different estrogen receptor isoforms should also be considered; thus, their response to vitamin D metabolites (and probably even analogs) differs from the classical ERα (66 kDa)-mediated pathway [13].…”
Section: Cell Linementioning
confidence: 99%
“…There are no uniform global guidelines on what vitamin D doses and serum concentrations should be considered as a target in the group of patients after breast cancer treatment. The National Comprehensive Cancer Network recommends that cancer patients should maintain 25(OH)D concentration above 30 ng/mL [56]. The American Cancer Society/American Society of Clinical Oncology recommends vitamin D supplementation in patients with breast cancer starting from the age of 50 at a dose of 600-1000 IU/day [22]; in turn, ESMO recommends higher daily doses of vitamin D in this group of patients, amounting to 1000-2000 IU/day [23].…”
Section: Discussionmentioning
confidence: 99%